Konstruksi Konsep Diri Dalam Realitas Sosial Pada Anggota Komunitas Stand-Up Indo Pasuruan - Mahmud, Mohammad; Ninuk Riswandari (Brand Communication, 2024)
This research explores how the comedy genres chosen by comics from the Stand Up Indo Pasuruan community reflect their self-concept construction. This research focuses on three comics, namely Resti Natasya, Mukti Irawan, and Ginaris Gangsar Pangestu, who each use the genres of dark/black comedy, observational comedy, and blue comedy as a medium to express their identity, personal experiences, and worldview. Using a qualitative approach with a case study method, data was collected through in-depth interviews, performance observation, and analysis of comedy material performed by the comics. The results show that the comedy genre serves not only as a means of entertainment, but also as a tool to navigate life experiences, build self-identity, and interact with social norms. Resti Natasya utilizes dark/black comedy and self-deprecating comedy to express self-acceptance and the transformation of difficult life experiences into acceptable humor. Mukti Irawan uses observational comedy to reflect everyday social reality through a comedic lens that simplifies the complexities of life. Meanwhile, Ginaris Gangsar Pangestu with blue comedy reveals taboo aspects of society, challenges social norms, and asserts courage in expression.